POMT2 mutations cause α-dystroglycan hypoglycosylation and Walker-Warburg syndrome. Issue 12 (13th May 2005) - van Reeuwijk, J; Janssen, M; van den Elzen, C; Beltran-Valero de Bernabé, D; Sabatelli, P; Merlini, L; Boon, M; Scheffer, H; Brockington, M; Muntoni, F; Huynen, M A; Verrips, A; et al.
Abstract : Background: Walker-Warburg syndrome (WWS) is an autosomal recessive condition characterised by congenital muscular dystrophy, structural brain defects, and eye malformations. Typical brain abnormalities are hydrocephalus, lissencephaly, agenesis of the corpus callosum, fusion of the hemispheres, cerebellar hypoplasia, and neuronal overmigration, which causes a cobblestone cortex. Ocular abnormalities include cataract, microphthalmia, buphthalmos, and Peters anomaly. WWS patients show defective O-glycosylation of α-dystroglycan (α-DG), which plays a key role in bridging the cytoskeleton of muscle and CNS cells with extracellular matrix proteins, important for muscle integrity and neuronal migration. In 20% of the WWS patients, hypoglycosylation results from mutations in either the protein O-mannosyltransferase 1 ( POMT1 ), fukutin, or fukutin related protein ( FKRP ) genes. The other genes for this highly heterogeneous disorder remain to be identified. Objective: To look for mutations in POMT2 as a cause of WWS, as both POMT1 and POMT2 are required to achieve protein O-mannosyltransferase activity. Methods: A candidate gene approach combined with homozygosity mapping. Results: Homozygosity was found for the POMT2 locus at 14q24.3 in four of 11 consanguineous WWS families. Homozygous POMT2 mutations were present in two of these families as well as in one patient from another cohort of six WWS families. Immunohistochemistry in muscle showed severely reduced levels of glycosylated α-DG, which is consistent with the postulated role for POMT2 in the O-mannosylation pathway. Conclusions: A fourth causative gene for WWS was uncovered. These genes account for approximately one third of the WWS cases. Several more genes are anticipated, which are likely to play a role in glycosylation of α-DG.